Fairy rescue : the fairies are in danger! - Rees, Gwyneth; Bannister, Emily (London : Macmillan Children's Books, 2007)
Maddie tries to help her friend Poppy, a flower fairy who lives in the woods behind her grandpa's house, and the other fairies after someone starts catching and imprisoning them.
5.2
3-6
3-6
Keywords: Fairies -- Juvenile fiction; Fairies -- Fiction; Fairies -- Fiction